PENGARUH VOLUME EMISI KARBON, PENGUNGKAPAN EMISI KARBON, PENGUNGKAPAN PRAKTIK MANAJEMEN EMISI KARBON TERHADAP KINERJA PERUSAHAAN - Sitti Adrati; Yvonne Augustine (Fakultas Ekonomi Universitas Tarumanagara, 2022)
This research aims to analyze the effect of volume of carbon emission, carbon emission disclosure and carbon management practice disclosure on company performance. This study used the size of the company as a control variable with a price to book value as an indicator. This research was conducted using multiple regression models with a sample of 151 companies from the Indonesian Sustainability Award in the period 2016 - 2018. The instrument of this research was adapted from CDP Questionnaires to score the disclosure of Carbon Management Practice. While emission carbon disclosure was a dummy variable and volume of carbon emission used the quantity of volume carbon emission was reported in sustainability reporting. The research found that volume of carbon emission has a negative relationship with firm performance while disclosure of carbon emission doesn’t have a relationship with firm performance. Disclosure of Carbon Management Practice has a positive relationship with firm performance using CDP Questionnaires as a tool of measurement.